Students’ Perception Toward the Use of E-LKPD Liveworksheets.com in Learning English at SMA N 7 Padang - Fiera Annisa; Nofrina Eka Putri (Journal of English Language Teaching, 2023)
Technology has already been part of education, especially in the teaching and learning process. Therefore, to support success in learning, teachers are required to master technology and utilize technology in designing lesson plan, delivering material, giving assignments, and assessing learning process. One of the uses of technology to realize those requirements is the use of electronic student worksheet (E-LKPD). One of the platforms that support E-LKPD is Liveworksheets.com. The purpose of this study is to find out the students’ perception toward the use of E-LKPD Liveworksheets.com viewed from Technology Acceptance Model (TAM): perceived usefulness, perceived ease of use, and attitude toward use. This research used descriptive with quantitative method. Questionnaire was used to collect the data. The results of this study show that students perceive usefulness, perceive ease of use, and have very positive perception toward the use of E-LKPD Liveworksheets.com in learning English, especially grammar. They found that E-LKPD Liveworksheets.com is effective and efficient, and it helps students improve their performance in learning grammar. E-LKPD Liveworksheets.com is easy to use and has flexibility in helping the students work on it. Furthermore, students felt happy and not bored while using E-LKPD Liveworksheets.com. Hence, the students have a very positive perception toward the use of E-LKPD Liveworksheets.com in grammar.